The privilege of taken for grantedness: On precarity and mobile media. (April 2023) - Ingraham, Chris; Grandinetti, Justin
This essay makes a case for more critical inquiry in mobile media research around the privilege of taken for grantedness. As a critical supplement to Richard Ling's important work on the taken for granted dispersion and embedment of technologies such as the mobile phone or automobile into everyday life, we examine the precarity that such reliance involves. Taking certain media for granted makes other, more invisible vulnerabilities harder to see and acknowledge. We make this case using the example of TikTok, a short-form mobile streaming app that has rapidly become a go-to social media platform worldwide—as well as a massively "visible" infrastructure due to its associated geopolitical tensions and security concerns. In light of recent conversations about banning the platform, TikTok offers an instructive case study for the privilege of taken for grantedness and the deceptively precarious nature of our mobile media practices.